2014
DOI: 10.1111/epi.12570
|View full text |Cite
|
Sign up to set email alerts
|

Seizure semiology and EEG findings in mitochondrial diseases

Abstract: SUMMARYObjective: Seizures constitute a frequent yet under-described manifestation of mitochondrial disorders (MDs). The aim of this study was to describe electroencephalography (EEG) findings and clinical seizure types in a population of children and adults with mitochondrial disease. Methods: Retrospective chart review of 165 records of children and adults with mitochondrial disease seen in the University of Texas Houston Mitochondrial Center between 2007 and 2012 was performed; all subjects were diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 14 publications
2
55
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9] Epilepsy resulting from MDs may manifest at any age and may be the presenting or prominent symptom in both syndromic (eg, Alpers-Huttenlocher syndrome (AHS), Leigh syndrome) and non-syndromic MDs. Epileptic seizures are one of the most frequent symptoms of CNS involvement due to mitochondrial dysfunction 1 with a prevalence rate ranging from 35% to 60%.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Epilepsy resulting from MDs may manifest at any age and may be the presenting or prominent symptom in both syndromic (eg, Alpers-Huttenlocher syndrome (AHS), Leigh syndrome) and non-syndromic MDs. Epileptic seizures are one of the most frequent symptoms of CNS involvement due to mitochondrial dysfunction 1 with a prevalence rate ranging from 35% to 60%.…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy is a common feature [3,10], although preceded by other clinical presentations in most cases [11]. In fact, mitochondrial dysfunction has been shown to both generate seizures as well as result in neuronal cell death [12]. Seizures can manifest at any age and be the presenting feature of an underlying biochemical defect.…”
Section: Introduction In Mitochondrial Disorders and Mitochondrialmentioning
confidence: 99%
“…Although there are no data on the exact prevalence of epilepsy in mitochondrial disorders, seizures are more common in some mitochondrial disorders than in others [10]. For example, in children with mitochondrial disorders the reported prevalence of seizures ranged between 35% and 61% [12]. Whittaker et al, found an overall prevalence of epilepsy of 23.1% in a prospective cohort of 182 adults with mitochondrial disease followed up for 7 years [14].…”
Section: Introduction In Mitochondrial Disorders and Mitochondrialmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MDs consist of a spectrum of disorders that can involve single or multisystem presentations, neurological symptoms are common clinical characteristics. In recent years, clinical, genetic, and biochemical studies have revealed an emerging link between mitochondrial dysfunction and neurodevelopmental disorders, including intellectual disability (ID) (Valenti et al, 2014) childhood epilepsy (Chevallier et al, 2014) and autism spectrum disorder (ASD) (Rossignol and Frye, 2012). Interestingly, these conditions have also been associated with interneuron dysfunction (Marin, 2012).…”
Section: Introductionmentioning
confidence: 99%